Dual inhibition of allosteric mitogen-activated protein kinase (MEK) and phosphatidylinositol 3-kinase (PI3K) oncogenic targets with a bifunctional inhibitor. Issue 7 (1st April 2015) - Van Dort, Marcian E.; Galbán, Stefanie; Wang, Hanxiao; Sebolt-Leopold, Judith; Whitehead, Christopher; Hong, Hao; Rehemtulla, Alnawaz; Ross, Brian D.
Graphical abstract: Abstract: The MAP kinase (Ras/MEK/ERK) and PI3K/Akt/mTOR oncogenic signaling pathways are central regulators of KRAS-mediated transformation. Molecular reciprocity between the Ras/MEK/ERK and PI3K/Akt/mTOR pathways provides cancer cells with the ability to evade treatment when targeting only one pathway with monotherapy. Multi-kinase targeting was explored through the development of a single bivalent chemical entity by covalent linking of high-affinity MEK and PI3K inhibitors. A prototype dual-acting agent (compound8 ) designed using the PI3K inhibitor ZSTK474 and the Raf/MEK inhibitor RO5126766 as scaffolds displayed high in vitro inhibition of both PI3K (IC50  = 172 nM) and MEK1 (IC50  = 473 nM). Additionally, compound8 demonstrated significant modulation of MEK and PI3K signaling pathway activity in human A549 human lung adenocarcinoma cells and pancreatic cancer cells (PANC-1) and also decreased cellular viability in these two cell lines.